DYLEMAT „ROSOMAKA”. PROBLEM PRZETARGU NA KOŁOWY TRANSPORTER OPANCERZONY DLA WOJSKA POLSKIEGO W ŚWIETLE PISMA „POLSKA ZBROJNA” I „RAPORTU MACIEREWICZA” - Smolarek, Paweł (In Gremium. Studies in History, Culture and Politics, 2008)
THE “ROSOMAK” DILEMMA: CONTROVERSY OVER THE SELECTION OF TENDER FOR THE ARMOURED PERSONNEL CARRIER FOR THE POLISH ARMY – AS DESCRIBED IN “POLSKA ZBROJNA” PERIODICAL AND IN “RAPORT MACIEREWICZA” PARLIAMENTARY REPORT S u m m a r y The battlefields of today require vehicles that can quickly and relatively safely deploy troops. Such a role is played by armored personnel carriers (APC) which facilitate transport and evacuation of soldiers, though using them does involve certain risks. With the modernization of the army underway, in order to improve the interoperation of the Polish Armed Forces, the decision was made to invite tenders for the APC for the Polish Army. The contract was won by a Finnish company, Patria Vehicles OY. Since its very beginning, the tender process stirred up controversy and raised many questions. The selection of the winning tender met with contradictory opinions. Relatively positive views on the vehicle were voiced in the military press. The weekly “Polska Zbrojna” stressed the carrier’s technical assets. Besides, this periodical expressed doubts concerning the future (or rather the prolonged process) of providing the Polish Armed Forces with the APC “Rosomak” – this being a result of flawed procedures and the fuss over the tendering for the arming of the vehicle. Nevertheless, the selected vehicle has doubtless improved the operational worth of the Polish troops. A different assessment of “Rosomak” can be found in the report on WSI, the military intelligence agency. According to the ‘Vetting Committee’, presided over by Antoni Macierewicz, the tender procedure glaringly violated the law and the selected vehicle did not meet the requirements for the manufacturer.